Последняя охота: Повести и рассказы / Ф. А. Абрамов - Абрамов Федор Александрович (Сов. Россия, 1973)
Экземпляры: Пф (1973) / Инвентарный номер: 51250с / Авт.знак: А 16 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4